Organoleptic and physical and chemical parameters of Nubian goats’ milk at mixed infection with gastrointestinal nematodes from the suborder Strongylata - I. I. Tsepilova; A. P. Konovalov; S. A. Shemyakova (Российский паразитологический журнал, 2023)
The purpose of the research is to determine the species composition of nematodes from the suborder Strongylata and to study organoleptic and physical and chemical parameters of the Nubian goats’ milk at strongylatoses of the digestive tract. Materials and methods. The study subjects were lactating Nubian goats aged 3 to 5 years from private farms in the Moscow Region. A total of 37 animals were examined. Faeces were studied by flotation methods per Fülleborn and KotelnikovKhrenov. To determine the species composition, partial helminthological dissections per K. I. Skryabin were used. In the infected animals from the experimental and control groups, organoleptic and physical and chemical milk parameters were studied prior to and after therapeutic measures using an anthelmintic with the active ingredient fenbendazole at a dose of 5 mg/kg. The deworming effectiveness was determined by the control test. Physical and chemical milk parameters were determined using an automatic Klever-2 milk analyzer, and organoleptic parameters were determined according to common methods pursuant to the effective GOST.Results and discussion. The lactating Nubian goats infected with gastrointestinal strongylates on the Moscow Region private farms amounted to 100% in the Podolsk Urban Okrug, and 88.2% in the Voskresensk Urban Okrug. The species composition was represented by 8 species, namely, Haemonchus сontortus, Ostertagia ostertagi, Trichostrongylus axei, T. colubriformis, Nematodirus spathiger, N. filicollis, Cooperia оvina, and Bunostomum trigonocephalum. In the pre- and postdeworming milk studies, the organoleptic parameters corresponded to the effective GOST in appearance, texture, color and smell; the sweetish taste was only absent after deworming in the experimental goats. Gastrointestinal nematodes from the suborder Strongylata did not affect the organoleptic parameters of milk. However, the pre- and posttreatment weight fraction of fat changed from 2.90±0.30 to 5.40±0.22% in the experimental group.